Interferon: History, Correlation, Mechanism, and limitation - Liu, Qilin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Nowadays, more and more patients suffer from cancer in clinical practice, which has become a hot topic in medical care. The researchers are struggling to find new cancer therapy. Cytokines are a group of protein molecules, and Interferon is the class of them. It has regulation and adjusting ability in the immune system. Moreover, in cancer research, it occupies a momentous role in its ability to combine with other drugs and special effects. Interferon was first found in the 20th century and is widely used in Melanoma, chronic myelogenous leukemia, and hepatocellular carcinoma therapy. In simple terms, Interferon possesses anti-tumor effects by regulating NK cells and T cells. It enhances antigen presentation and supervises the immune system. Additionally, it inhibits tumor angiogenesis, triggers apoptosis and necrosis, and alters the tumor micro-environment. However, Interferon isn’t denying that having some limitations like side effects, potential risk, bottlenecks and high costs. These may cause patients to get injured. To discuss these aspects, the essay will be based on the research made before and summarize them to get conclusions. Besides, it also uses comparison to argue the issues. The research has shown that although Interferon has different functions and a long period of research, it is still in active research to find new contributions now, and patients may use the new drug or therapy one day to Interferon’s ramifications.